Numerical seismic analysis of CEB structures - Stavole, Martina (2019)
Earth has always been widely used as building material all around the world, as a solution to the needs of poor and rural lifestyle of population. Over the years, earthen materials have been revalued as a good economic and sustainable choice for developing countries. One of the most important improvement in the earthen construction technologies field is represented by compressed earth blocks (CEBs). Nevertheless, even if it is an improvement of traditional building techniques, the seismic vulnerability of these constructions still requires further understanding. The aim of the present paper is to numerically investigate the seismic response of one-story CEB masonry buildings by performing incremental dynamic analyses (IDA). In particular, three different models are examined in order to consider the influence of structural elements, such as internal partition walls and a ring beam. The obtained results are compared in the paper with the ones carried out by using static pushover analyses.